2006
DOI: 10.1523/jneurosci.3062-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Spikes in Basal Dendrites of Layer 5 Pyramidal Neurons during Action Potential Bursts

Abstract: Patch-clamp recording from dendrites has lead to a significant increase in our understanding of the mechanisms underlying signal integration and propagation in neurons. The majority of synaptic input to neurons, however, is made onto small-diameter dendrites, currently beyond the scope of patch-clamp recording techniques. Here we use both calcium and voltage imaging to investigate propagation of action potentials (APs) in fine basal dendrites of cortical layer 5 pyramidal neurons. High-frequency (200 Hz) AP bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
7

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 44 publications
7
96
7
Order By: Relevance
“…Both Ni 2C at low concentration and NMDA receptor antagonists precluded this spike-timing dependent plasticity indicating that the large and long-lasting dendritic depolarization evoked by the T-(R) mediated action potential bursts allows the development of synaptic NMDA currents which contribute to LTP induction. 36,37 The importance of T-(R) burst evoked dendritic spikes for the antidromic propagation of action potentials and the induction of synaptic plasticity was also demonstrated at the synapses between layer 2/3 neurons and layer V pyramidal neurons. Addition of low Ni 2C concentration or intracellular application of QX-314 that blocked action potentials precluded the induction of the LTD evoked when pairing action potential bursts in layer V pyramidal neurons with extracellular synaptic stimulations of layer 2/3 neurons.…”
Section: Activation Of T-type Channels Mediates Membrane Depolarizatimentioning
confidence: 99%
See 1 more Smart Citation
“…Both Ni 2C at low concentration and NMDA receptor antagonists precluded this spike-timing dependent plasticity indicating that the large and long-lasting dendritic depolarization evoked by the T-(R) mediated action potential bursts allows the development of synaptic NMDA currents which contribute to LTP induction. 36,37 The importance of T-(R) burst evoked dendritic spikes for the antidromic propagation of action potentials and the induction of synaptic plasticity was also demonstrated at the synapses between layer 2/3 neurons and layer V pyramidal neurons. Addition of low Ni 2C concentration or intracellular application of QX-314 that blocked action potentials precluded the induction of the LTD evoked when pairing action potential bursts in layer V pyramidal neurons with extracellular synaptic stimulations of layer 2/3 neurons.…”
Section: Activation Of T-type Channels Mediates Membrane Depolarizatimentioning
confidence: 99%
“…In these dendritic regions which receive the majority of synaptic inputs, 35 the T-(R) bursts lead to a supra-linear increase in intracellular calcium compared to the generation of single action potentials or trains of spikes at lower frequencies. 36,37 Interestingly, at the synapses between layer V pyramidal cells, pairing unitary excitatory postsynaptic potentials (EPSPs) with high-frequency action potential bursts, but not single action potentials, induced a robust LTP. Both Ni 2C at low concentration and NMDA receptor antagonists precluded this spike-timing dependent plasticity indicating that the large and long-lasting dendritic depolarization evoked by the T-(R) mediated action potential bursts allows the development of synaptic NMDA currents which contribute to LTP induction.…”
Section: Activation Of T-type Channels Mediates Membrane Depolarizatimentioning
confidence: 99%
“…Using this method to compare the first and third action potential signal in a burst, a recent study concluded that action potentials are significantly attenuated as they propagate into distal The increasing delay between the signal from the somatic region and proximal dendritic segments reflects the time taken for the propagation of the action potential to dendritic locations. Taken from [2] basal dendrites of pyramidal neurons [26], in contrast to the conclusions of Antic [5].…”
Section: Voltage Imaging Using Internally Applied Dyesmentioning
confidence: 93%
“…Adapted from [44] in the contribution of the basal fluorescence signal to the voltage-sensitive signal, leading to differences in the magnitude of the percentage change in fluorescence at different locations, even if the underlying voltage change is the same. One way to get around this problem is to compare relative changes in voltage-sensitive dye signals in response to different stimuli at the same location [14,26]. Using this method to compare the first and third action potential signal in a burst, a recent study concluded that action potentials are significantly attenuated as they propagate into distal The increasing delay between the signal from the somatic region and proximal dendritic segments reflects the time taken for the propagation of the action potential to dendritic locations.…”
Section: Voltage Imaging Using Internally Applied Dyesmentioning
confidence: 99%
“…In CA pyramidal neurons, Kv4.2 channels are distributed in dendrites, postsynaptic sites, and the soma, whereas Kv1.4 subunits are expressed in axon branches [25][26][27][28] . Therefore, it is possible that the somatic regulation of Kv4.2 subunits and their trafficking may exhibit patterns similar to those in dendrites, where synaptic plasticity activity-dependently regulates the redistribution of Kv4.2 channels in an activity-dependent manner.…”
Section: Introductionmentioning
confidence: 99%